THE EFFECT OF VISUALIZATION, AUDITORY AND KINESTHETIC (VAK) MODEL TOWARD THE STUDENTS’ ABILITY IN WRITING PROCEDURE TEXT AT GRADE IX MTsN 1 REGENCY OF INDRAGIRI HULU - Destri Wahyuningsih, Maysa Witari, (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
Abstract :The purpose of this research were to find out is there any significant effect of Visualization, Auditory and Kinesthetic (VAK) Model toward Writing Skill of Procedure Text at Great IX Mtsn 1 Regency of Indragiri Hulu. This is an Experimental research. The research was carried out in MTsN 1 Indragiri Hulu from September 20th 2018 at grade IX MTsN 1 Regency of Indragiri Hulu. The data collection techniques in this research are observation, test, and documentation. Technique sampling in this research is simple random sample technique. The samples of this research were class IX.4 (Experimental Class) and IX.6 (Control Class) of School at MTsN 1 Regency of Indragiri Hulu. Every class consisted of 30 students. The instrument used to collect the data is test (Pretest and Post test). The data analysis in this research is used t-test. Based on the calculating of t-test that the out put independent samples Test shows Equal Variances Assumed which can be seen from the number of the